Apocalyptic sheep and goats in Matthew and 1 Enoch - Lafitaga, Elekosi F. (Emory studies in early christianity, 2022)
"Matthew's eschatological imageries of judgment are often identified as apocalyptic and referred to as Matthew's apocalyptic discourses. In this volume Elekosi F. Lafitaga reexamines Matthew's vision of the sheep and goats in the judgment of the nations, which are often interpreted as metaphors for the saved and the condemned. Lafitaga views these images in the wider context of the rhetoric of apocalyptic communication stretching back to Matthew 3. This broader context reveals that the vision of Matthew 25 serves to exhort Israel in the here and now according to the Torah, with salvation for Israel involving an indispensable responsibility to love and serve humanity. Central to Lafitaga's analysis is the highly probable scenario that the material in Matthew is dependent on the Book of Dreams (1 Enoch 83-90)"--